The Role Anesthesiologist in Management of Obstetric Haemorrhage: A Literature Review - Shantikaratri, Emilia T.; H, Ruddi; Isngadi (Majalah Anestesia & Critical Care, 2024)
Hemorrhagic shock in obstetrics is still a major cause of maternal mortality and morbidity worldwide. Recognition of bleeding in obstetric patients is complicated by the normal physiologic changes that occur during pregnancy. Visual estimates of blood loss are often erroneous and underestimated because of contamination with amniotic fluid, or internal or hidden blood loss. Thus, careful clinical observation and a high index of suspicion are required for the early detection and management of obstetric hemorrhage. The usage of ultrasound (US) is considered as the first line method for detecting abnormal condition which might serve as a predictor for hemorrhagic shock. Despite of careful risk assessment given, obstetric-specific bleeding protocols, such as resuscitation and blood transfusion, are required to facilitate the integration and timely escalation interventions. The intervention of choice for hemorrhagic shock in obstetrics encompasses a wide variety of options, such as the usage of tranexamic acid, cell salvage, resuscitative endovascular balloon occlusion of the aorta (REBOA), anesthetic management, and surgical, as well as radiological provides multiple available approach, each with their own risk and advantages. The purpose of this review is to describe the management of obstetric hemorrhage from anesthetic point of view, encompassing the identification of patients at risk, resuscitative management, and perioperative management.